IMPLEMENTASI PEMBERLAKUAN HUKUM SASI DI DESA NEGERI LIMA - Ismail Kaliky (Jurnal Studi Islam, 2020)
Sasi in practice is known as Rule Affairs (Prohibition of State) is Sasi implemented by the State Government of Lima, after agreement with the Community. Villagers State Lima, until today still exist apply SASI culture as ancestral heritage. Problems in this research is, how the application of sanctions in the village of Negeri Lima SASI, and How to view Islamic law against the imposition of sanctions in the village SASI Negeri Lima. The research method is descriptive qualitative. The results showed that, in the village Sasi Application of sanctions imposed against the object of State Lima SASI nutmeg and coconut, with a form of penalties penalties amount of money that has been set respectively for nutmeg Rp. 500 perbiji and coconuts Rp. 10.000, - apiece, are intended to provide protection to the sustainability and protection of nutmeg and coconut fruit that is harvested at the appointed time. In this case, the new harvest can be done after the open SASI. That sanctions SASI given to the offender provisions of SASI, does not conflict with the provisions of Islamic law, application of the SASI and sanctions SASI against the thieves, in line with the provisions of Islamic law, in particular the study of jurisprudence against the punishment of hand amputation for thieves.